2003
DOI: 10.1071/ar02083
|View full text |Cite
|
Sign up to set email alerts
|

Maximising the use of soil water by herbaceous species in the high rainfall zone of southern Australia: a review

Abstract: Abstract. The planting of deep-rooted pasture species, herbaceous shrubs, and trees has been widely recommended to reduce deep drainage and recharge to the groundwater in the high rainfall zone (HRZ). However, in more recent years, the value of perennial pastures to reduce recharge has been questioned in areas with >600 mm annual rainfall. Currently, pastures dominated by annual species with relatively low productivity occur across much of the HRZ where deep drainage is most likely contributing to recharge. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Overgrazing on drought‐stressed pastures in summer and autumn is the major cause of poor pasture persistence in southern Australia (Beattie, 1994). Saul et al (1998) reported that rotational grazing generally had positive effects on the persistence of perennials with most notable benefits with phalaris. Barker et al (1991) found that the persistence of orchardgrass was improved under rotational grazing.…”
Section: Management and Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…Overgrazing on drought‐stressed pastures in summer and autumn is the major cause of poor pasture persistence in southern Australia (Beattie, 1994). Saul et al (1998) reported that rotational grazing generally had positive effects on the persistence of perennials with most notable benefits with phalaris. Barker et al (1991) found that the persistence of orchardgrass was improved under rotational grazing.…”
Section: Management and Persistencementioning
confidence: 99%
“…Whereas grasses with summer dormancy are sought for survival and persistence, there is need for complementary pasture species or alternative ways to supply feed over summer to fulfi ll animal requirements. Indeed, there is demand for plants that can actively grow in summer to fi ll feed gaps or exploit moisture deep in the soil profi le for groundwater recharge control (Singh et al, 2003;Nie et al, 2004a). Under these circumstances, it is desirable to have plants that are both summer active and persistent, although this goal seems diffi cult to achieve in temperate (or cool-season) grasses.…”
Section: Summer Dormancy and Persistencementioning
confidence: 99%
“…While the roots of Lp are no larger than 1.0 m deep, the roots of Bv reach 1.5 m in depth (Stewart, 1996, Nie et al, 2008. The latter is relevant since deeper root systems can reach water from deeper soil horizons (Singh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The way grasslands are managed can have major impacts on the water cycle, ecosystem function and biomass production. In Australia, solutions to these problems lie in increasing the longevity of plants in the landscape (Singh et al 2003). Perennial-dominated grasslands fulfil two roles in water management – they efficiently utilize soil water, due to deeper root systems and longer growing seasons than annual species, and they can protect the soil surface from soil and nutrient loss, particularly during high intensity short-duration storms.…”
Section: Introductionmentioning
confidence: 99%